ChemInform Abstract: A General Solution for the 2-Pyridyl Problem - Dick, Graham R.; Woerly, Eric M.; Burke, Martin D. (ChemInform, 2012)
The cross‐coupling of air‐stable 2‐pyridyl MIDA boronates with a variety of aryl halides and triflates under conditions A) is highly efficient for the preparation of various functionalized pyridine derivatives bearing aryl substituents at position 2.